Variability in Aonla (Emblica officinalis Gaertn.) Accessions Collected from Panna Forests of Madhya Pradesh - Pandey, D.; Shukla, S.K.; Kumar, Akhilesh (Indian Journal of Agroforestry, 2020)
Explorations were conducted in north and south Panna forest areas and adjoining villages of Madhya Pradesh to identify superior aonla genotypes with good fruit quality during the years 2004-2005 and 2005-2006. A total number of thirty five genotypes of aonla having economically important horticultural traits were identified. Observations on the physicochemical parameters of fruits were recorded. These genotypes showed considerable variability with respect to morphological and physico-chemical characters. Analysis of fruits revealed fruit weight from 10.27-48.90 g; fruit length from 2.53 to 3.83 cm; fruit diameter from 2.57 to 4.63 cm; TSS from 8.67 to 17.0Â 0Brix; acidity from 1.38 t0 3.33%; vitamin C content from 292.72 to 750.12 mg/100g pulp; tannin contents from 2.59 to 6.76%; reducing sugars from 2.29 to 4.62%; total sugars from 4.06 to 6.94%; TSS : acid ratio from 3.22 to 7.35 and sugar: acid ratio from 1.51 to 4.17. As regards mineral contents of fruits, nitrogen content from 0.56 to 2.24%; phosphorous from 0.12 to 1.72%; potassium from 0.39 to 1.09%; calcium from 0.067 to 0.280%; magnesium from 552.10 to 1153.00 ppm; copper from 1.31 to 4.66 ppm; manganese from 4.91 to 35.14 ppm; sodium from 19.13 to 1291.00 ppm; zinc from 2.80 to 26.40 ppm and iron from 11.14 to 97.00 ppm were recorded in different germplasm accessions collected. On the basis of overall assessment, it was concluded that natural aonla trees in Panna forests have good amount of variability with respect to physico-chemical traits. Seven aonla genotypes, viz. T5 ,T7, T11, T15, T24, T33 and T34 were found most promising and these might be used either as superior trees for clonal multiplication or as superior gene source in further breeding programmes.